PENGARUH EFIKASI DIRI DAN PILIHAN KARIR TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI: (Studi Pada Karyawan Generasi Z PT. Bank Muamalat Indonesia) - Agustina, Priyastiti Nawa; Ahmad, Gofur (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
The aim of this research is to analyze the influence of self-efficacy and career choice on employee performance both directly and indirectly through the mediating influence of job satisfaction. Data was collected by distributing questionnaires using Google Form via electronic mail or the WhatsApp application. Data were analyzed using the Structural Equation Model (SEM) tool using the SmartPLS apps version 4 to analyze both direct and mediation effect. A total of 157 Gen Z employees of PT Bank Muamalat Indonesia who work in Head Office, Region Jakarta West, and Region Jakarta East participated as respondents in this research sample. The results of this research show that there is a positive and significant influence between self-efficacy on career choice, between self-efficacy and career choice on job satisfaction, and self-efficacy and job satisfaction on employee performance. Meanwhile, the influence of career choice on employee performance is positive but unsignificant. The research results also show that there is a positive and significant influence between self-efficacy and career choice on employee performance when it is mediated by job satisfaction. The results of this research provide information to organizations how important to create programs and policy that can improve the employees’ satisfaction, especially Gen Z employees. Organizations can also take advantages from their Gen Z employees’ high self-efficacy and social skills to support them achieve organizational goals.Keywords: Employee performance, job satisfaction, self-efficacy, career choice